2015
DOI: 10.1002/anie.201408891
|View full text |Cite
|
Sign up to set email alerts
|

CH Functionalization of Phenols Using Combined Ruthenium and Photoredox Catalysis: In Situ Generation of the Oxidant

Abstract: A combination of ruthenium and photoredox catalysis allowed the ortho olefination of phenols. Using visible light, the direct C-H functionalization of o-(2-pyridyl)phenols occurred, and diverse phenol ethers were obtained in good yields. The regeneration of the ruthenium catalyst was accomplished by a photoredox-catalyzed oxidative process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(61 citation statements)
references
References 71 publications
3
53
0
5
Order By: Relevance
“…Subsequently, Rueping demonstrated that photoredox catalysis could also aid Ru- and Rh-catalyzed oxidative Heck reactions in a mechanistically analogous manner. 91,92 …”
Section: Metallaphotoredox Catalysis: C–c Bond Formationmentioning
confidence: 99%
“…Subsequently, Rueping demonstrated that photoredox catalysis could also aid Ru- and Rh-catalyzed oxidative Heck reactions in a mechanistically analogous manner. 91,92 …”
Section: Metallaphotoredox Catalysis: C–c Bond Formationmentioning
confidence: 99%
“…The details of the oxidation have not yet been elucidated, but given the two-electron oxidation state change required, the mechanism must presumably be somewhat more complicated than a simple bimolecular photoinduced single electron transfer. Rueping has utilized a similar design strategy in oxidative Heck reactions of aryl amides 252 and phenols 253 catalyzed by rhodium and ruthenium, respectively.…”
Section: Photoinduced Electron Transfermentioning
confidence: 99%
“…One year later, this group published a similar method for alkenylation of phenols. 54 The directed ortho C-H activation of phenols were allowed by Ru/Ag catalyst mixture, while Ir visible-lightphotoredox catalysis functionalized as electron transfer system. The C-H activation-photoredox dual catalyzed cyclization reactions are providing prominent opportunity to prepare complex molecules exclusively.…”
Section: C-h Activation and Photoredox Dual Catalysismentioning
confidence: 99%